Gāyatripuraścaranapaddhatih - Śaṅkarācārya (Ānandāśramasaṃskrtagranthāvaliḥ, 1980)
Manuals of Hindu rituals for the efficacy of the Vedic hymn (mantra) Gāyatrī and the worship of its presiding deity Gāyatri.